Development of an Illustrated Module for Dental Health Education Enhancement in Islamic Boarding Schools - Sinaredi, Betadion Rizki; Bramantoro, Taufan; Firmansyah, Fikri Febrian; Cahyaningtyas, Carissa Putri; Firdausi, Nurul Layly (Faculty of Dental Medicine Universitas Airlangga, 2023)
Backgrounds: Dental and oral health problems in adolescents are increasing in Indonesia, as evidenced by the highest dental health problems of 73.5%. Purpose: to develop an illustrated module on dental health education for adolescents at the Isy Karimah Imtaq Islamic Boarding School, Karanganyar Regency, Central Java. Method: The illustrated module socialization activity was held in September 2022 at Imtaq Shighor Isy Karimah, Karanganyar Regency, Central Java with 30 students as participants. Evaluation is done by giving a pre-test and post-test that has been filled out by the participant. Result: Based on the results of the evaluation, it was found that the average pre-test score was 69.2 while the post-test was 78.8, and the increase in participant knowledge was 6.9. Conclusion: students who participated in the socialization of the illustrated module experienced an increase in dental health knowledge for adolescents at the Islamic Boarding School.